Dual-Path Effects of the Relationship between Multiple Identities and Employee Innovative Behavior: The Moderating Role of the Situational Aesthetic - Chiang, Yen-Feng; Tsai, Chi-Tung; Peng, Jui Chih; Lin, Sz-Yan (Technium Social Sciences Journal, 2023)
Multiple identities of employees are different and will tangibly or intangibly influence innovative behavior of employees. Based on social identity theory, this study examines the relationship between multiple identities of employees and innovative behavior of dual paths (future time perspective and work-family conflict), and further explores whether employees have a moderating effect on the aforementioned relationship under the situational aesthetic. In this study, 1,019 cross-industry employees were selected as research objects. Results include: (1) the higher the level of multiple identities, the more the employees exhibit innovative behavior; (2) the future time perspective mediates the relationship between multiple identities and innovative behavior; (3) multiple identities reduce the performance of employees’ innovative behavior through increases in work-family conflict.; and (4) the situational aesthetic has a moderating effect on the relationship between work-family conflict and innovative behavior. When the situational aesthetic is high, the higher the employee’s work-family conflict, the greater the employee’s innovative behavior. By contrast, when the situational aesthetic is low, the higher the employee’s work-family conflict, the lower their innovative behavior. Finally, this study discusses the theoretical and managerial implications.